APPLICATION OF OPEN-SOURCE GRAPHIC PROGRAMS IN UZBEK FINE ARTS EDUCATION: METHODOLOGY FOR INCREASING THE CREATIVE COMPETENCE OF FUTURE TEACHERS - Avazjon Abdumajitov (Modern American Journals, 2025)
This study is dedicated to testing a specially designed methodology for integrating open-source and free graphic software (Krita, Sketchbook) into the educational process to enhance the creative competence of future fine arts teachers within the framework of the "Teacher of the Future" concept. The relevance of the research is determined by Uzbekistan's state policy on education digitalization and the need to bridge the gap between traditional art education and modern labor market demands. The study was conducted as a pedagogical experiment using a pre-test/post-test control group design. It involved 60 students (N=60) from the Visual Arts program at Chirchik State Pedagogical University. The experimental group (n=30) was trained for 15 weeks using the enhanced methodology with graphic software, while the control group (n=30) followed the traditional curriculum. Adapted Torrance Tests of Creative Thinking were used to evaluate results. Statistical analysis (independent samples t-test) revealed that the experimental group demonstrated significantly higher scores in all components of creativity (fluency, flexibility, originality) compared to the control group (p<.001). The findings confirm that the proposed methodology not only significantly enhances students' creative abilities but also equips them with modern digital tools, thereby improving their professional competence.
Keywords: Creative competence, graphic software, Krita, Sketchbook, visual arts education, pedagogical methodology, digital integration, teacher of the future, Uzbekistan, pedagogical experiment.